New dopaminergic therapies for PD motor complications. (15th February 2022) - Larson, Danielle; Simuni, Tanya
Abstract: Background: Motor complications, characterized by "off" periods – when anti-parkinsonian medications are ineffective – and dyskinesia, are the hallmark of advanced Parkinson's disease (PD). While levodopa is the gold standard PD medication in terms of efficacy, its short duration of effect coupled with progressive loss of dopaminergic neurons leads to motor complications and fails to treat off periods. Purpose of review: This review focuses on novel dopaminergic therapies that were recently made clinically available or are currently in development for the treatment of motor complications. First, it will discuss rescue therapies for the treatment of off episodes, including novel apomorphine and levodopa formulations. Second, it will highlight adjunctive dopaminergic medications approved to reduce total daily off time. Third, it will discuss longer-acting levodopa formulations in development and introduce a novel selective dopamine agonist under study. Finally, it will cover novel dopaminergic delivery mechanisms, with specific focus on continuous subcutaneous infusions in development. Summary: The breadth of dopaminergic therapies recently approved or in development for motor complications, and specifically off time reduction, evokes cautious optimism. Gains in reducing off time with rescue therapies, adjunctive medications or longer-acting levodopa formulations are modest, and underscore the need for more continuous dopaminergic delivery to address the underlying pathophysiology and translate to clinically meaningful improvement in motor complications. This article is part of the Special Issue on 'New therapeutic approaches to Parkinson's disease'. Highlights: Two rescue-therapies have been approved for rapid treatment of off-symptoms: inhaled levodopa and sublingual apomorphine. Longer-acting levodopa formulations are being studied for their potential to reduce daily off time. Subcutaneous levodopa infusion aims to provide more continuous dopamine delivery and assuage motor complications. Novel dopaminergic compounds that selectively target D1/D5 receptors are being developed.